Ivacaftor for the Treatment of Cystic Fibrosis Coexisting with Trisomy 21: A Case Report - Charbek, Edward (Cureus, 2019)
The association between cystic fibrosis (CF) and trisomy 21, or Down Syndrome (DS) is rare, and it pertains a poor prognosis with the majority of patients dying in infancy. We report a case of a 28-year-old male with DS and moderate CF (ΔF508/G551D, FEV1 1.92 L, 60% predicted at the age of 18 years) diagnosed in childhood. The patient’s lung function continued to deteriorate over time (FEV1 nadir of 1.29 L), and he was started on ivacaftor in the year 2012 following ivacaftor release and approval. FEV1 and FVC improved significantly along with an increase in the patient’s body mass index. Ivacaftor potentiates the open-channel probability of the G551D-CFTR. It has been shown to improve lung function, symptoms, weight, and sweat chloride concentration and decrease the risk of pulmonary exacerbations in patients with severe pulmonary CF (G551D). Our case argues against the reported literature of poor prognosis when the two chronic diseases coexist as only one case report in the literature described a DS patient with CF surviving into adulthood. In our patient, treatment with ivacaftor resulted in an increase in FEV1 and weight that exceeded the response observed in the ivacaftor landmark trial. Genetic studies are underway to understand the genetic basis of the large variation in DS phenotypes, which is probably caused by allelic heterogeneity on multiple chromosomes. The latter may explain the enhanced response observed in our patient and suggests that although patients with concomitant DS and CF may have worse lung disease, their response to novel therapies may be intensified. Further studies are needed in this subset of patient population to better characterize CF with trisomy and other genetic disorders.